Are Nectarines to Blame? A Case Report and Literature Review of Spontaneous Bacterial Peritonitis Due to Listeria monocytogenes - How, Joan (Conn Med, 2015)
Spontaneous bacterial peritonitis (SBP) is a frequent and potentially deadly complication of ascites in patients with end-stage liver disease. Unlike other pathogens more commonly implicated in SBP, Listeria monocytogenes is a nonenteric organism that may be acquired either sporadically or in the setting of foodborne outbreaks. Listeria is an unusual cause of SBP that presents particular management challenges because of the organism’s intrinsic resistance to first-line and empiric SBP treatment that would otherwise include third-generation cephalosporins. We present here a case of Listeria SBP in a 68-year-old man with previously unidentified cirrhosis. His infection occurred in the context of a nationwide fruit recall for Listeria contamination, prompting an epidemiologic investigation. After describing the case, we then review the extant literature on Listeria peritonitis. To date, no case studies on Listeria SBP have systematically described risk factors for Listeria acquisition. As incidence of Listeria SBP is increasing, however, knowledge of patient risk factors, especially foodborne exposure risks, may be important in preventing future episodes of Listeria SBP, and in accurately monitoring foodborne outbreaks.